2004
DOI: 10.1074/jbc.m409216200
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic Domain Crystal Structure of Protein Kinase C-θ (PKCθ)

Abstract: A member of the novel protein kinase C (PKC) subfamily, PKC, is an essential component of the T cell synapse and is required for optimal T cell activation and interleukin-2 production. Selective involvement of PKC in TCR signaling makes this enzyme an attractive therapeutic target in T cell-mediated disease processes. In this report we describe the crystal structure of the catalytic domain of PKC at 2.0-Å resolution. Human recombinant PKC kinase domain was expressed in bacteria as catalytically active phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 41 publications
7
137
0
3
Order By: Relevance
“…7 molecular basis of A-loop phosphorylation in controlling catalytic activity has been revealed with the publication of the crystal structures of the kinase domains of PKC , PKC and PKC II : phosphorylation at the A-loop makes important contributions in stabilising the active conformation of these kinases by forming ionic contacts with positively-charged residues in the vicinity of the kinase domain [27][28][29].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…7 molecular basis of A-loop phosphorylation in controlling catalytic activity has been revealed with the publication of the crystal structures of the kinase domains of PKC , PKC and PKC II : phosphorylation at the A-loop makes important contributions in stabilising the active conformation of these kinases by forming ionic contacts with positively-charged residues in the vicinity of the kinase domain [27][28][29].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Molecular modelling studies have shown that the negatively charged phosphate at the HM site on PKC II and PKC forms hydrogen bonds with an invariant glycine residue and thus serves to stabilise the enzyme [27,29]. While this phosphorylation site is not conserved in aPKCs, the negatively charged glutamic acid residue at the HM site on PKC performs a similar function [28].…”
Section: Hydrophobic-motif Phosphorylationmentioning
confidence: 99%
“…Interaction energies of adjacent beads are harmonic in bond length and angle, with the geometry of the native state included through a dihedral term and non-local bead-bead interaction terms. Non-local contacts are included via (4) which has a minimum of depth ε n at r = σ ij , with σ ij being the native distance between the C α (i) and C α (j) atoms in the crystal structure. In homogenous structure-based models, there is a single value for ε n .…”
Section: Construction Of the Energy Functionmentioning
confidence: 99%
“…The activity of many signal transducing proteins is associated with large conformational changes. For example, C-terminal Src Kinase protein [2], the Cyclin Dependent Kinase family [3], the Protein Kinase C family [4] and Adenylate Kinase (AKE) [5] have stable inactive conformations, in addition to active forms. Since the balance between conformations regulates protein activity, conformational transitions play important roles in the machinery of the cell [6].…”
Section: Introductionmentioning
confidence: 99%
“…A estrutura cristalográfica do domínio catalítico das PKCs só foi resolvida em 2004 (Xu et al, 2004). O domínio catalítico é bastante conservado nas quinases em geral, possuindo cerca de 250 aminoácidos que formam os lóbulos N e C. O lóbulo N é composto principalmente por folhas  e também possui uma alça rica em glicinas responsável por ligar o ATP e posicionar o fosfato  para a catálise.…”
Section: Figura 1 Esquema Das Estruturas Primárias E Terciárias Das unclassified